Diagnostic Utility of Lymphoid Enhancer Binding Factor 1 Immunohistochemistry in Chronic Lymphocytic Leukaemia/ Small Lymphocytic Lymphoma - V L, Vishnu; M, Simi C; A. Nair, Rekha; Sara George, Preethi; A V, Jayasudha; Mary Jacob, Priya (Asian Pacific Journal of Cancer Care, 2025)
Objective: Chronic lymphocytic leukaemia/small lymphocytic lymphoma (CLL/SLL) is a common mature B-cell neoplasm composed of monomorphic small mature B cells co-expressing CD5 and CD23. Diagnosis is based on morphologic evaluation and immunophenotyping, but no specific immunohistochemical marker is availableTo evaluate the usefulness of LEF1 in the diagnosis of CLL/SLL by immunohistochemistry and in distinguishing CLL/SLL from other small B-cell lymphomas. Methods: Previously diagnosed 120 cases of small B cell lymphomas by IHC/flowcytometry from 1st January 2017 to 31st December 2019 in the RCC, Thiruvananthapuram are included in the study. This includes thirty diagnosed cases of CLL/SLL (lymph node/ bone marrow trephine biopsies). Thirty cases of follicular lymphoma, 30 cases of mantle cell lymphoma and 30 cases of marginal zone lymphoma are also included in the study for comparison. Clinical details, morphological features and IHC already done for these cases (CD20, CD5, CD23 and cyclin D1) were analysed. IHC for LEF1 is done in all 120 cases using Rabbit (EP310) monoclonal antibody. Data is entered into excel sheet and analysis is done using SPSS software. Result: LEF1 has 100% sensitivity, specificity, NPV, PPV, and accuracy for diagnosing CLL/SLL, with a diagnostic cut-off of 100%, compared to other immunomarkers. Conclusion: LEF1 is a highly specific and sensitive diagnostic marker for CLL/SLL, aiding in the differential diagnosis of small B-cell lymphomas.